Frontline bortezomib and rituximab for the treatment of newly diagnosed high tumour burden indolent non‐Hodgkin lymphoma: a multicentre phase II study. (25th April 2014) - Evens, Andrew M.; Smith, Mitchell R.; Lossos, Izidore S.; Helenowski, Irene; Millenson, Michael; Winter, Jane N.; Rosen, Steve T.; Gordon, Leo I.
Summary There is a lack of published data examining non‐cytotoxic options for the frontline treatment of patients with high‐tumour burden (HTB) indolent non‐Hodgkin lymphoma (iNHL). We completed a multicentre phase II study for patients with untreated HTB iNHL (NCT00369707) consisting of three induction cycles of weekly bortezomib and rituximab followed by an abbreviated consolidation. Forty‐two patients were treated and all were evaluable; the most common histology was follicular lymphoma (FL) (n = 33, 79%). Patient characteristics included median age 62 years (40–86); 38% bulky disease; 19% malignant effusions; 91% advanced‐stage disease; and median FL International Prognostic Index (FLIPI) score was 3. Therapy was well tolerated with few grade 3/4 toxicities including minimal neurotoxicity. On intent‐to‐treat, the overall response rate (ORR) at end of therapy was 70% with a complete remission (CR) rate of 40% (FL: ORR 76%, CR 44%). With 50‐month median follow‐up, 4‐year progression‐free survival (PFS) was 44% with 4‐year overall survival (OS) of 87% (FL: 44% and 97%, respectively). Four‐year PFS for FLIPI 0–2 vs. 3–5 was 60% vs. 26% respectively (P = 0·02), with corresponding OS rates of 92% and 81% respectively (P = 0·16). Collectively, bortezomib/rituximab is a non‐cytotoxic therapeutic regimen that was well tolerated and resulted in long‐term survival rates approximating prior rituximab/cytotoxic chemotherapy series for untreated HTB FL.